Love as Inquiry: An Autoethnographic Story About My Engagement with Arts-Informed Research - Flemming, Christina (Art/Research International, 2025)
Four years ago, I was invited to take on the position of managing editor for Art/Research International (ARI). As we celebrate the tenth anniversary of ARI, I seek to honour the voices that have informed my own engagement with arts-informed research. As an artful researcher, who is comparatively new to the academy, I wish to centre the importance of looking back in order to look forward. In this article, I slow down and trace my own steps. I honour the guidance that I received having Dr. Ardra Cole as my doctoral supervisor. I detail my process conceptualizing and defending an autoethnographic dissertation containing a collection of stories about coming out as queer later in life. I offer one of the stories from my dissertation, and reflect on how my own work was informed by the question posed by Pauline Sameshima and Carl Leggo (2013), “what does love have to do with education?” (p. 90).